Perbedaan Hasil Belajar Kritik Tari Dengan Menggunakan Sistem Penilaian Educandy dan Quizziz Pada Siswa Kelas X di SMK Negeri 27 Jakarta - Nandita, Dhea; Triana, Dinny Devi; Oktarini, Selly (Jurnal Pendidikan Tari, 2024)
The purpose of this study was to differentiate the learning outcomes of dance criticism using the Educandy and Quizziz scoring systems. The population is class X students at SMK Negeri 27 Jakarta and a sample of 20 students. The sampling technique uses purposive sampling. Based on the results of the study it can be concluded that: There are differences in Learning Outcomes of Dance Criticism using a scoring system. Based on theoretical studies and testing of data on learning outcomes of Dance Criticism using Quizziz and Educandy, it can be concluded that the results are as follows: The results of hypothesis testing obtained are the average values ​​with using Educandy 77.25 while the average score using Quizziz is 79.50 so that it can be said that learning using Quizziz is higher than learning with Educandy on the learning outcomes of dance criticism at SMK Negeri 27 Jakarta